The temporal pattern of recovery in eccentric hamstring strength post-soccer specific fatigue. Issue 3 (3rd July 2019) - Rhodes, David; McNaughton, Lars; Greig, Matt
ABSTRACT: Eccentric hamstring strength is an aetiological risk factor for soccer injury. The temporal pattern of recovery post-exercise is critical in injury management. 18 male professional soccer players completed baseline assessments of eccentric hamstring strength at isokinetic speeds of 60, 150 and 300°· s −1 . Post SAFT 90 measures were repeated immediately, + 24 hrs, + 48 hrs and + 72 hrs. Main effects for recovery time and testing speed in average torque (AvT), peak torque (PT) and the corresponding angle (Ɵ) were supplemented by regression modelling to describe the temporal pattern of recovery. A main effect for isokinetic testing speed was observed in PT and AvT. A main effect for recovery time highlighted greater strength pre-exercise, with a quadratic pattern to temporal recovery highlighting minima achieved at between 40–48 hrs. Strength parameters are not fully recovered until 96 hrs post soccer specific fatigue, with implications for training design and injury management, particularly within fixture-congested periods.